2014
DOI: 10.1590/s1806-37132014000300004
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen desaturation during the six-minute walk test in COPD patients

Abstract: Objective: To evaluate the behavior of oxygen saturation curves throughout the six-minute walk test (6MWT) in patients with COPD. Methods: We included 85 patients, all of whom underwent spirometry and were classified as having moderate COPD (modCOPD, n = 30) or severe COPD (sevCOPD, n = 55). All of the patients performed a 6MWT, in a 27-m corridor with continuous SpO2 and HR monitoring by telemetry. We studied the SpO2 curves in order to determine the time to a 4% decrease in SpO2, the time to the minimum SpO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
1
15
1
1
Order By: Relevance
“…The BODE is considered an index of multidimensional (24,25), classification of the severity of COPD (26,27) where a score of 3 points or more is associated 3 to 4 points; Quartile III: 5 to 6 points; Quartile IV: 7 to 10 points.…”
Section: Resultsmentioning
confidence: 99%
“…The BODE is considered an index of multidimensional (24,25), classification of the severity of COPD (26,27) where a score of 3 points or more is associated 3 to 4 points; Quartile III: 5 to 6 points; Quartile IV: 7 to 10 points.…”
Section: Resultsmentioning
confidence: 99%
“…Functional status assessment revealed that walk distance in patients with BAF was significantly lower as compared to those with anthracosis only. In addition, on 6MWT more than half the BAF patients (58.3%) desaturated with a fall in SpO 2 ≥ 4% from the baseline which was considered significant [11]. On functional assessment, patients with BAF fared poorer than those with anthracosis, a finding which is yet to be documented in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Patients in Group 1 walked significantly lesser distance as compared to Group 2 (p = 0.003) but there was no significant difference between Groups 1 and 3 (p = 0.41) and Groups 2 and 3 (p = 0.09). In Group 1, significant desaturation (a fall in SpO 2 ≥ 4% from the baseline) [11] was seen in 14/24 (58%) patients, in Group 2 6/17 (35.3%) and in Group 3 6/19 (31.6%).…”
Section: Six Minute Walk Test (6mwt)mentioning
confidence: 97%
“…We also observed patients who showed a reduction in SpO 2 > 4% from baseline, whether or not the resultant SpO 2 was less than 94% (13). Even though this latter criterion is often used in quantifying the severity of obstructive sleep apnoea in sleep studies (14), it has also been used for assessment of patients with chronic obstructive pulmonary diseases (COPD) and in the context of endoscopic procedures (15,16).…”
Section: Discussionmentioning
confidence: 99%